Biosafety and beyond: GM crops in India - Mistry, Percy S. (2006)
The finance ministry and Planning Commission going head to head in a battle over the integrity of Fiscal Responsibility Budget Management targets will inevitably result in a "lose-lose" outcome. Why do the finance minister and deputy chairman of the Planning Commission not consider the possibility of another "golden rule" for guaranteeing public fiscal rectitude that would achieve both their aims? - Reproduced.
Keywords: Public finance; Public finance